Comparison of modified hybrid strength training and neuromuscular electrical stimulation on joint position sense in healthy untrained individuals: A randomized controlled trial - Anastrinia Syafiqah Hanun; Damayanti Tinduh; Nurul Kusuma Wardani (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Low physical activity reduces muscle strength and proprioception, increasing injury risk. Neuromuscular electrical stimulation (NMES) and hybrid training aim to enhance proprioception by strengthening muscles. This study compared the effects of a modified hybrid strength training program and Russian protocol NMES on knee joint position sense (JPS) in healthy, untrained men. Methods: Sixteen untrained males were randomly allocated to either the hybrid training group or the NMES group. Both groups exercised three times a week for four weeks. An isokinetic dynamometer was used to measure JPS at 30° and 60° on both dominant and non-dominant legs before and after the intervention. Results: Both interventions significantly improved JPS across all tested angles. In the hybrid group, improvements were observed in the dominant leg at 30° (p = 0.028) and 60° (p = 0.009), and in the non-dominant leg at 30° (p = 0.033) and 60° (p = 0.008). The NMES group showed similar improvements at 30° and 60° in both legs (p < 0.05). No significant differences were found between groups. Conclusion: Modified hybrid strength training and Russian protocol NMES both enhanced knee JPS in healthy, untrained men, with neither proving superior. Larger trials are needed to confirm comparative effectiveness and explore clinical applications.